Penilaian Viabilitas Miokardium Dengan Dobutamine Stress Echo - Ignatius Yansen; Amiliana Mardiani; Ario Soeryo Kuncoro (Jurnal Kardiologi Indonesia, 2011)
The prevalence of left ventricular (LV) dysfunction and resultant heart failure is increasing in developing countries. Two thirds of cases of left ventricular dysfunction are the result of coronary artery disease (CAD). Although there have been significant advances in medical therapy for LV dysfunction and resulting symptoms of heart failure, the prognosis from heart failure remains extremely poor. Many of these patients had previous myocardial infarctions, the extent of remaining viable tissue is of clinical interest, and also related to prognosis. Thus assessing myocardial viability is very important in patient with left verntricuar dysfunction to choose the right management. Dobutamine stress echo is one of the most common tool that used to asses myocardial viability.A 67 years old patient with chronic heart failure because of old anterior and inferior MCI with low ejection fraction. It is very important to assess the viability in patients with advanced heart failure to know the future management because it is related to patient’s morbidity and mortality. With little viable myocard in this patient, the best management for this patient is conservative therapy with medical therapy. Dobutamine stress echocardiography therefore, may well provide complementary information in the assessment of myocardial viability. Future modalities are now being studied to give more objective measurement of myocardial viability with higher sensitivity and specificity.